Amniotic Band Syndrome, Perinatal Hospice, and Palliative Care versus Active Management - Shadi Rezai; Justin Faye; Annika Chadee; Sri Gottimukkala; Ruchi Upadhyay; Carla Lara; Benamanahalli H. Rajegowda; Andrew D. Corwin; Rasila V. Lala; Jessica Vernon; Dilfuza Nuritdinova; Stephen Chasen; et al. (Case Reports in Obstetrics and Gynecology)
Introduction. Amniotic band syndrome and sequence are a relatively rare condition in which congenital anomalies occur as a result of the adherence and entrapment of fetal parts with coarse fibrous bands of the amniotic membrane. A large percentage of reported cases have an atypical gestational history. The frequency of this obstetric complication is not affected by fetal gender, genetic abnormality, or prenatal infection. Case. A 21-year-old, G1P0 female parturient at 18 weeks and 5 days with a single intrauterine gestation during a routine ultrasound evaluation was noted to have amniotic band sequence. The pregnancy was subsequently complicated by preterm premature rupture of membranes with oligohydramnios, resulting in a surviving neonate scheduled for rehabilitative treatment. Conclusion. Amniotic band syndrome is an uncommon congenital anomaly resulting in multiple disfiguring and disabling manifestations. Several theories are proposed with most involving early rupture of the amnion and entanglement of fetal parts by amniotic bands. This syndrome can be manifested by development of multiple malformations, with the majority of the defects being limb abnormalities of a disorganized nature, as in the case we present. In the absence of a clear etiology of consequential congenital abnormalities, obstetric management guidelines should use shared decision models to focus on the quality of life for the offspring.